The Evolution Of Doctor-Nurse Relationships: From Hierarchy To Partnership. An Update (Journal of Namibian Studies : History Politics Culture, 2022)
The relationship between doctors and nurses has evolved significantly over time, transitioning from a hierarchical structure to one characterized by partnership and collaboration. This evolution reflects changes in healthcare delivery, professional roles, and societal attitudes towards healthcare professionals. This article explores the historical context, factors driving change, and the current state of doctor-nurse relationships. It examines the benefits of partnership-based relationships, challenges encountered, and strategies for fostering effective collaboration in modern healthcare settings.